Comparative Study of Easement and Compensation Values Case Study on the Construction of Trans Adriatic Pipeline-TAP - Taka, Alda; Musabelliu, Bahri (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2017)
A comparative study of the easements and compensation values of fruit trees in the cases of pipeline crossing has been undertaken for Albania, Greece, Turkey, Georgia, Azerbaijan and Armenia. The purpose of the study was to compare assessment methodologies for important land use elements during construction and operation phases of pipelines. Investors in the case of pipeline construction demand land for purchase, rent, right of way or easement for tree planting restriction in the range of 8 m. In this study, only two types of compensation are compared: (i) easement and (ii) fruit tree compensation values. Discussion of the methods and their calculation formulas show that there are differences in easement quotes. They were equal to 50% of the land value in Albania, Greece and Turkey and 60% of the land value in the other countries. In fruit tree compensation, the value differences were even greater due to the application of different methods. They were the lowest in Albania and Turkey compared to other countries. However, in all cases, the compensation and easement rates were in accordance with national legislation and met the basic principle of the property right use and the fair compensation of easements and fruit trees sacrificed by the works. Keywords: replacement, easement, pipeline construction, economic impact, engineering.